PENERAPAN APLIKASI SIMULASI ELECTRONIC WORKBENCH DAN PROTEUS PADA MATERI PENERAPAN RANGKAIAN ELEKTRONIKA BAGI SISWA KELAS XI TEKNIK ELEKTRONIKA INDUSTRI - Siti Nurhidayah; Didik Aribowo; Desmira Desmira (JPTE FT UNY, 2020)
ABSTRACT:The purpose of this research was to determine student learning outcomes after the application of EWB software learning media during the learning process in the subject of applying electronic circuits; knowing student learning outcomes after the application of proteus software learning media during the learning process in the subject of applying electronic circuits; knowing the difference in student learning outcomes after the application of EWB and proteus software learning media in the subject of implementing electronic circuits. This type of research is an experiment with experimental research method (experimental) and pretest-posttest control group design. The population in this study were students of class XI SMKN 1 Cikande majoring in Industrial Electronics Engineering which consisting of 38 students. The research sample consisted of 2 classes with a total of 21 students and 17 students. The sampling technique used in this research is saturated sampling technique. Data collection instruments used were is pretest and posttest and psychomotor observation sheets. Data analysis technique used the Mann Withney test (U-test) to test the hypothesis with SPSS version 21.0. The results of this study suggests that (1) there are differences in learning outcomes in cognitive aspects between students treated with EWB and proteus. The average student learning outcomes in the cognitive aspects of the proteus were 73.23, greater than the average student learning outcomes in the cognitive aspects of the EWB, which was 68.1. Uji-U calculations obtained sig. (2-tailed) of 0,000. If the value is sig. (2-tailed) is less than alpha 0.05, then the H0 statement is rejected and H1 is accepted. (2) there are differences in psychomotor learning outcomes between students treated with proteus and EWB. The average student learning outcomes of the psychomotor aspects treated with the proteus were 82.06, greater than the average learning outcomes of students in the psychomotor aspects treated with the EWB, namely 75.48. Uji-U calculations obtained sig. (2-tailed) of 0,000. If the value is sig. (2-tailed) less than alpha 0.05, then the H0 statement is rejected and H1 is accepted.ABSTRAK:Tujuan penelitian ini adalah mengetahui hasil belajar siswa setelah diterapkan media pembelajaran software EWB dalam mata pelajaran penerapan rangkaian elektronika; mengetahui hasil belajar siswa setelah diterapkan media pembelajaran software proteus dalam mata pelajaran penerapan rangkaian elektronika; mengetahui perbedaan hasil belajar siswa setelah diterapkan media pembelajaran software EWB dan proteus dalam mata pelajaran penerapan rangkaian elektronika. Jenis penelitian yang digunakan yaitu eksperimen dengan metode penelitian eksperimen (eksperimental) dan desain pretest-posttest control group design. Populasi dalam penelitian ini adalah siswa kelas XI SMKN 1 Cikande jurusan Teknik Elektronika Industri yang terdiri dari 38 siswa. Sampel penelitian terdiri dari 2 kelas dengan total 21 siswa dan 17 siswa. Teknik pengambilan sampel yang digunakan dalam penelitian ini teknik sampling jenuh. Instrumen pengumpulan data yang digunakan adalah pretest, posttest dan lembar observasi psikomotor. Teknik analisis data menggunakan uji Mann Withney (Uji-U) untuk menguji hipotesis dengan SPSS versi 21.0. Hasil penelitian ini menunjukkan bahwa (1) ada perbedaan dalam hasil belajar aspek kognitif antara siswa yang diperlakukan dengan EWB dan proteus. Rata-rata hasil belajar siswa aspek kognitif proteus sebesar 73,23 lebih besar dibandingkan rata-rata hasil belajar siswa pada aspek kognitif EWB yaitu sebesar 68,1. Perhitungan Uji-U diperoleh hasil sig. (2-tailed) sebesar 0,000. Jika nilai sig. (2-tailed) kurang dari alpha 0,05, maka pernyataan H0 ditolak dan H1 diterima. (2) ada perbedaan hasil belajar ranah psikomotor antara siswa yang diberi perlakuan dengan proteus dan EWB. Rata-rata hasil belajar siswa aspek psikomotor yang diberi perlakuan proteus sebesar 82,06 lebih besar dibanding dengan rata-rata hasil belajar siswa aspek psikomotor yang diberi perlakuan EWB yaitu sebesar 75,48. Perhitungan Uji-U diperoleh hasil sig. (2-tailed) sebesar 0,000. Jika nilai sig. (2-tailed) kurang dari alpha 0,05, maka pernyataan H0 ditolak dan H1 diterima.